Keberpihakan Pengaturan Hak Atas Informasi Publik dalam Undang-Undang Keterbukaan Informasi Publik - Fauzin (Law Faculty of Universitas Bandar Lampung, 2011)
Ratification Law No. 14 of 2008 on Transparency of Public Information, one aim is for the right of every citizen to obtain public information found its legal basis. It turns out insurance against all citizens of the right to obtain public information still find many obstacles. In general implications for the strengthening of law is the right to information and the principles of disclosure of information, but it still containe the crucial article that can be a source of weakness and bad for the public, among others: Article 4 paragraph (3), Article 24 paragraph (1); and Article . Law is in general settings set new things related to the protection guaranteed right to public information. But at the same time there are also articles that threaten the right for information for citizens. The substance of the articles that are not biased against citizens in the process of submitting requests for- information and a mechanism for filing an objection is not simple. The existence of the article can be a source of criminalization for applicant information law is contrary to the goal itself, which wanted to increase community participation in the implementation of the State.